GOALS AND OBJECTIVES OF TEACHING A FOREIGN LANGUAGE IN SECONDARY SCHOOL - Kobilov Zafarjon Zokirovich; Nasimova Sohiba Yaxyayevna (KONFERENSIYALAR, 2025)
Abstract. The practical goal of teaching a foreign language at school is to form the foundations of practical knowledge of foreign languages in students. Achieving the goals and solving the tasks set is carried out with the help of various teaching aids, acting in a certain, methodically determined system.